EVALUASI TERHADAP ASPEK KEBERSIHAN DAN KESUCIAN DALAM PERANCANGAN ARSITEKTUR MASJID - Bahar, Moh. Arsyad (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2012)
Cleanliness and purity are two of primary things in Islam. Moslems are supposed to maintain their cleanliness and purity in every aspect of their lives. In mosques, cleanliness of place is one of the most important aspects to be concerned because it is closely related to worship activities. However, mosques architecture these days are more concern about the aesthetical aspect rather than the cleanliness aspect. In this paper, an evaluation for the islamic cleanliness (thaharah) aspect has been explained for some great mosques, i.e. Jami’ Mosque Malang, an-Nur Mosque Pare Kediri, and A.R. Fachruddin Mosque Muhammadiyah University of Malang. In these great mosques, the cleanliness and the purity problems often appear because of the failure in design, such as the position and the design of toilet, the thaharah system, the visitors’ circulation, the building maintenance, etc. Because of these problems, a design guideline which has a priority in the aspect of cleanliness that can be applied in other mosques’ architectural design is also described in this paper.Keywords: thaharah, mosque architecture, cleanliness